Vita & Virginia the love story that inspired Virginia Woolf's Orlando - Button, Chanya director; Arterton, Gemma 1986-; Debicki, Elizabeth 1990-; Rossellini, Isabella 1952-; Atkins, Eileen 1934- (Thunderbird Releasing, 2019)
Vita & Virginia is the true story of the passionate relationship between literary trailblazer Virginia Woolf (Elizabeth Debicki), and the enigmatic aristocrat Vita Sackville-West (Gemma Arterton). The film tells the story of the birth of the novel their intoxicating encounters inspired; Woolf's bold experiment in art and androgyny, Orlando
Original: Großbritannien, Irland 2018
Keywords: Sackville-West, V. / (Victoria) / 1892-1962 / Drama; Woolf, Virginia / 1882-1941 / Drama; Sackville-West, V. / (Victoria) / 1892-1962; Woolf, Virginia / 1882-1941; Women authors, English / Drama; Female friendship / Drama; Lesbians / Drama; Female friendship; Lesbians; Women authors, English; Film; DVD-Video